Boxing Pandora : rethinking borders, states, and secession in a democratic world - Waters, Timothy William, 1966- (Yale scholarship online., 2020)
A timely and provocative challenge to the foundations of our global order: why should national borders be unchangeable? The inviolability of national borders is an unquestioned pillar of the post-World War II international order. Fixed borders are believed to encourage stability, promote pluralism, and discourage nationalism and intolerance. But do they? What if fixed borders create more problems than they solve, and what if permitting borders to change would create more stability and produce more just societies? Legal scholar Timothy Waters examines this possibility, showing how we arrived at a system of rigidly bordered states and how the real danger to peace is not the desire of people to form new states but the capacity of existing states to resist that desire, even with violence. He proposes a practical, democratically legitimate alternative: a right of secession. With crises ongoing in the United Kingdom, Spain, Ukraine, Iraq, Syria, Sudan, and many other regions, this reassessment of the foundations of our international order is more relevant than ever.